MORPHOFUNCTIONAL STATE OF RAT VISCERAL WHITE ADIPOSE TISSUE UNDER OBESITY DEVELOPMENT AND SILVER NANOPARTICLES ADMINISTRATION - PUSTOVALOV, A.; TKACHENKO, O.; MATVIIENKO, M.; DZERZHYNSKY, M. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
There was studied the morphofunctional state of the visceral white adipose tissue of rats with obesity and after introduction of silver salt solution and silver nanoparticles solution. In particular, we analyzed the morphofunctional changes in the visceral white adipose tissue of rats on a high-calorie diet, as well as the effects of the silver nitrate solution and the silver nanoparticles solution at a dose of 1 mg / 1 kg body weight and 0.5 mg / 1 kg body weight on the morphofunctional state of the visceral white adipose tissue of rats on a high-calorie diet. There were established morphofunctional changes in cells of the rats white adipose tissue on the high-calorie diet and with the introduction of silver preparations in different concentrations. The condition of the adipose tissue was evaluated on the basis of the following parameters: the relative mass of the visceral fat, the cross-sectional area of adipocytes, the relative number of adipocytes per unit area. There were compared effects of administration to animals with obesity of the silver nitrate solution at a dose of 1 mg / 1 kg body weight and 0.5 mg / 1 kg body weight, as well as a of the silver nanoparticles solution at a dose 1 mg / 1 kg body weight and 0.5 mg / 1 kg of body weight. All the above silver preparations reduced the manifestations of obesity in animals which were maintained in a high-calorie diet. In addition to the form of the silver preparation (silver nitrate solution or silver nanoparticle solution), its concentration is important. The highest efficiency was shown after the administration of the silver nanoparticles solution at a dose 0.5 mg / 1 kg of body weight. In rats of this experimental group, the studied parameters not only reached the control values, but they also exceeded them, which indicates expressed influence of the drug on the obesity manifestations. In addition, the rats showed signs of fat depletion.